The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/raq.12717
|View full text |Cite
|
Sign up to set email alerts
|

Creatine: A valuable supplement in aquafeeds?

Abstract: Creatine is an amino acid derivate commonly found in vertebrate muscle tissue. Creatine facilitates the recycling of adenosine triphosphate and thus contributes to the energy supply of the muscles as well as the brain. Creatine is used as a supplement for several reasons and its effects in humans, particularly in sports medicine, have been studied excessively. Also, creatine supplementation has been studied for its functions and benefits in terrestrial farm animals. Up to date, little is known about the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 126 publications
(378 reference statements)
0
4
0
Order By: Relevance
“…In an aqueous environment, fish swim almost constantly, which requires a relatively large amount of energy for muscle movement. The synthesis of creatine from glycine in the skeletal muscle of fish may promote more efficient coupling with local energy metabolism for physiological functions (e.g., constant swimming [ 32 ]) when compared with terrestrial mammals and birds, because guanidinoacetate is formed and further converted into creatine in the same muscle fiber. Because activities of creatine-synthesizing enzymes in HSB were upregulated by the dietary intake of glycine, it is crucial that diets must provide sufficient glycine to support creatine synthesis in fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an aqueous environment, fish swim almost constantly, which requires a relatively large amount of energy for muscle movement. The synthesis of creatine from glycine in the skeletal muscle of fish may promote more efficient coupling with local energy metabolism for physiological functions (e.g., constant swimming [ 32 ]) when compared with terrestrial mammals and birds, because guanidinoacetate is formed and further converted into creatine in the same muscle fiber. Because activities of creatine-synthesizing enzymes in HSB were upregulated by the dietary intake of glycine, it is crucial that diets must provide sufficient glycine to support creatine synthesis in fish.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures the maintenance of whole-body homeostasis that is essential for life in animals including fish. Furthermore, by serving as a component of a major energy buffer system, creatine is crucial for supporting fish-specific burst swimming [ 32 ]. Thus, compared with terrestrial farmed animals, creatine may play a more important role in the growth and survival of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine improves the circulation of adenosine triphosphate, which contributes to the supply of energy to the brain and muscles. 17 It has been found that adding creatine to plant feed can improve growth performance and promote growth. [18][19][20] In solutions at relatively low pH and high temperature, creatine is rapidly degraded to creatinine, whereas in the alimentary tract of aquatic products, degradation is greatly reduced or stopped.…”
Section: Identification Of Distinctive Compounds Among Different Habi...mentioning
confidence: 99%
“…Creatine is synthetized in two steps, catalyzed by L-arginine glycine amidinotransferase and guanidinoacetate N-methyltransferase in kidney and liver, respectively [36]. Carnitine is synthetized from peptide bound trimethyllysine, that after being hydrolyzed, are transformed to butyrobetaine and transported to the liver for hydroxylation to carnitine [16].…”
Section: Methionine and Synthesis Of Carnitine And Creatinementioning
confidence: 99%